A phase I/II trial of brentuximab vedotin plus rituximab as frontline therapy for patients with immunosuppression-associated CD30+ and/or EBV + lymphomas. Issue 14 (6th December 2021) - Pearse, William B.; Petrich, Adam M.; Gordon, Leo I.; Karmali, Reem; Winter, Jane N.; Ma, Shuo; Kaplan, Jason B.; Behdad, Amir; Klein, Andreas; Jovanovic, Borko; Helenowski, Irene; Smith, Sonali M.; et al.
Abstract: Treatment strategies for post-transplant lymphoproliferative disorders (PTLD) consist of response-adapted risk-stratified methods using immunosuppression reduction, immunotherapy, and chemotherapy. We investigated the efficacy of Brentuximab vedotin given concurrently with Rituximab (BV + R) once weekly for four weeks, followed by optional consolidation, and up to one year of maintenance. Among 20 assessable patients, BV + R therapy resulted in an overall response rate of 75% (95% CI 51 to 91, p = 0.044) with 60% achieving a complete response. Median time to best response was 28 days. Two-year progression-free survival and overall survival rates were 75 and 90%, respectively. Most common severe grade 3/4 treatment-related toxicities included neutropenia (40%), hypertension (30%), infection (25%), and peripheral neuropathy (15%). BV + R is a novel and effective therapeutic strategy that achieved rapid and durable remissions in previously untreated PTLD patients; however, this treatment platform requires further modification due to the high rates of treatment-related toxicity. Key points: Brentuximab vedotin + Rituximab showed ORR and CR rates of 75 and 60% in patients with immunosuppression-associated lymphoid malignancies High rates of treatment delay were attributed to treatment-related toxicity; further dosing optimization of this regimen is required